A4_1 Cool Orbit - Buckland, Jools; Crosby, Matthew; James, Oliver; Pearce, Rebecca (Physics Special Topics, 2017)
The IPCC estimates the average temperature of the Earth will rise between 2 K and 4 K by 2090-2099. If the radius of the Earth's orbit was increased, so less radiation from the Sun is received, global average temperatures would drop. We calculated that to negate the temperature increase of 2 K to 4 K, the radius of the Earth's orbit would have to be increased to 1.016 AU to 1.032 AU. Using a Hohmann transfer, to increase Earth's semi-major-axis to between 1.016 AU and 1.032 AU, the Earth's total velocity change was calculated to be between 235.5 m/s and 465.4 m/s.